2021
DOI: 10.3390/nitrogen2040027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating APSIM-and-DSSAT-CERES-Maize Models under Rainfed Conditions Using Zambian Rainfed Maize Cultivars

Abstract: Crop model calibration and validation is vital for establishing their credibility and ability in simulating crop growth and yield. A split–split plot design field experiment was carried out with sowing dates (SD1, SD2 and SD3); maize cultivars (ZMS606, PHB30G19 and PHB30B50) and nitrogen fertilizer rates (N1, N2 and N3) as the main plot, subplot and sub-subplot with three replicates, respectively. The experiment was carried out at Mount Makulu Central Research Station, Chilanga, Zambia in the 2016/2017 season.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 50 publications
0
17
0
2
Order By: Relevance
“…The study revealed that high nitrogen levels and early sowing dates combined with the high-yielding cultivar increased regional production. Chisanga et al, (2021a) also noted the significance of the interaction of sowing dates and nitrogen fertilization on maize yield and yield components in the Zambian agricultural landscapes. Sowing dates affect the accumulated temperature units and duration of radiation interception, which influences nitrogen uptake and utilization efficiency (Caviglia et al, 2014).…”
Section: Simulation Of Agricultural Management Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study revealed that high nitrogen levels and early sowing dates combined with the high-yielding cultivar increased regional production. Chisanga et al, (2021a) also noted the significance of the interaction of sowing dates and nitrogen fertilization on maize yield and yield components in the Zambian agricultural landscapes. Sowing dates affect the accumulated temperature units and duration of radiation interception, which influences nitrogen uptake and utilization efficiency (Caviglia et al, 2014).…”
Section: Simulation Of Agricultural Management Strategiesmentioning
confidence: 99%
“…The DSSAT modelling system includes the Crop Environment Resource Synthesis (CERES-Maize) model used for simulating maize (Zea mays L.) growth and yield under various environmental conditions. The model has been used to address a range of applications, such as evaluating strategies to cope with limited weather and soil conditions , evaluating climate change impacts on crop production (Babel & Turyatunga, 2015;Jiang et al, 2021;Lin et al, 2015), optimizing agronomic practices for increased production (Mubeen et al, 2016), and assessing the performance of various cultivars and their suitability in different environmental conditions (Chisanga et al, 2021c;Feleke et al, 2021). Researchers have tested the model under various production environments such as the Tropical, the Mediterranean, and Temperate regions (Ahmad et al, 2021;Arefi et al, 2017;Banterng et al, 2010;Getachew et al, 2021;Kothari et al, 2019;Vilayvong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop simulation model genetic coefficient development and calibration are vital for establishing their credibility and ability in simulating growth, development, yield attributes and yield of crops [32]. Among the four varietal genetic coefficients (Table 3) generated during the Rabi season of 2019-20, the time between emergence to flower appearance (EM-FL) and time between the first flower to first pod (FL-SH) ranged from 17.50 to 19.00 photothermal days and 7.00 to 8.00 photothermal days, respectively.…”
Section: Genetic Coefficient Development and Calibration Of Dssat Modelmentioning
confidence: 99%
“…However, the simulation of wheat grain yield and grain N at application of 150kg N/ha and soil organic carbon was poor. Several researchers have reiterated that, an adequately calibrated DSSAT models is a useful decision support management tool for assessing and predicting crop yield, nitrogen uptake, and other parameters [16,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%